The beta subunit of tomato fruit polygalacturonase isoenzyme 1: isolation, characterization, and identification of unique structural features. - Zheng, L (1992)
We have purified and isolated cDNAs encoding the beta subunit of tomato fruit polygalacturonase isoenzyme 1 (PG1), a cell wall protein that associates with, and apparently regulates, the catalytic PG2 polypeptides. Expression of the beta subunit is fruit specific and temporally separated from the expression of PG2 during fruit development. The 37- to 39-kD beta subunit is encoded as a 69-kD precursor protein containing a signal sequence and two propeptide domains. The mature protein is composed almost entirely of the novel 14-amino acid motif FTNYGxxGNGGxxx in which many of the phenylalanine residues are post-translationally modified. The unique structural features of the motif suggest an important role in the function of the protein and hence in the activity of PG1. The beta subunit may represent a class of bifunctional plant proteins that interact both with structural components of the cell wall and catalytic proteins to localize and/or regulate metabolic activities within the cell wall.